The Trend in Types of Tree Damage in Mangrove Forest Management Areas, East Lampung Regency - Rahmat Safe'i; Hari Kaskoyo; Ferdy Ardiansyah (CV. Literasi Indonesia, 2022)
Damage to mangrove trees is one of them influenced by the types of tree damage. The more types of tree damage to a single mangrove tree, the worse the health level of the mangrove tree will be. This study aims to obtain damage index trend values and types of tree damage in the east coast mangrove forest area, East Lampung Regency. Measurement of the types of damage to mangrove trees was carried out three times using the Forest Health Monitoring (FHM) method in two FHM cluster plots for each mangrove forest area. Assessment of damage to mangrove trees uses the Damage Index formula. The results showed that the trend index values for mangrove tree damage were 9.3 and 4.5 (Resort Kuala Penet, Way Kambas National Park), 9.2 and 19.8 (Margasari, Labuhan Maringgai), and 6.2. and 9.8 (Purworejo, Pasir Sakti) with the dominant types of damage being open wounds (code 03) 343 damage, damaged foliage/shoots (code 24) 240 damage, and broken/dead (code 22) 158 damage. Thus, the trend of damage index and types of damage to mangrove trees in the east coast mangrove forest area of East Lampung Regency has increased.